Buzzed : the straight facts about the most used and abused drugs from alcohol to ecstasy - Kuhn, Cynthia; Swartzwelder, Scott; Wilson, Wilkie; Wilson, Leigh Heather; Foster, Jeremy (New York, NY : W.W. Norton, 2008)
Incorporates the latest findings on such topics as energy drinks, prescription medications, and the date-rape drug GHB, in a volume that features quick-reference summaries, reports on how drugs enter the body and manipulate the brain, and entries on their short- and long-term effects.
pt. I. Alcohol -- Caffeine -- Ecstasy -- Hallucinogens -- Herbal drugs -- Inhalants -- Marijuana -- Nicotine -- Opiates -- Sedatives -- Steroids -- Stimulants -- pt. II. Brain basics -- Drug basics -- Addiction -- Legal issues.
Includes bibliographical references (p. 298-307) and index.
Keywords: Drugs of abuse -- Popular works; Substance-Related Disorders -- Popular Works; Nervous System -- drug effects -- Popular Works; Street Drugs -- Popular Works